The man from Mittelwerk - Urlocker, M. Z. (Inkshares, Inc, 2022)
1950. The Cold War simmers, and exGI Jack Waters is called in to investigate a fatal accident at a research lab in California. When Waters recognizes the victim, he realizes he must revisit his hidden past in World War II to solve a murder and prevent Nazi scientists from creating a terrible, new weapon in America. Blending noir detective fiction with post-WWII history, The Man from Mittelwerk builds from the facts of Operation Paperclip, the U.S. governments secret recruitment of 1,600 top Nazi scientists, to pose a dark what-if scenario. --